Employee Engagement and Leader-Member Exchange Private College Staff: Understanding Things That Can Help Employees Achieve Job Satisfaction and Organizational Citizenship Behavior in the Workplace - Diana Hayati; Zakhyadi Arifin (Cita Konsultindo Research Center, 2024)
ABSTRACT This study wants to determine the influence of employee engagement (EE) and leader-member exchange (LMX) on organizational citizenship behavior (OCB) with job satisfaction (JS) as a mediating variable in private university education personnel. The study delved deeper into how EE and LMX can improve job satisfaction and OCB, where previous studies have yielded mixed results. This research method with data was collected through an online survey of 100 staff working at a private university and analyzed using a structural equation model (Smart PLS). The results showed a direct influence on the variables EE on JS, EE on OCB, JS on OCB, and LMX on OCB, which showed a positive and significant influence, while LMX on JS had no significant effect. Meanwhile, the indirect influence can be seen from the influence of the EE-JS-OCB variable of 0.260 (positive) with a P-value of 0.000 < 0.05 (significant), meaning that JS plays a role in mediating the influence of EE on OCB. (H6). The indirect influence of LMX-JS-OCB is 0.048 (positive) with a P-value of 0.0193> 0.05 (insignificant), meaning that JS does not play a role in mediating the influence of LMX on OCB (H7). Research that discusses the relationship between work attachment variables, LMX, job satisfaction, and OCB has been done a lot, but no studies have been conducted on private university staff in South Kalimantan. Therefore, this study will discuss the relationship between work attachment variables, LMX, job satisfaction, and OCB of private university staff in South Kalimantan. Keywords: Employee engagement, LMX, Job Satisfaction and OCB